ANALYSIS OF THE SOURCES OF FORMATION OF THE WASTE ELECTROLYTES OF THE ELECTROLYTE PRODUCTION AND METHODS OF THEIR PROCESSING - Залыгина, Ольга; Журавская, Наталья; Чепрасова, В.И. (Modern engineering and innovative technologies, 2022)
The paper analyzes the sources of formation of waste electrolytes from galvanic production. The necessity of separate disposal of rinsing waste water and waste electrolytes with their subsequent processing is shown. Possible options for processing waste